The Effect Of Psychological Empowerment On Employee Performance Work Engagements Imediation: Study Of Education Personnel Affected By Equalization Of Echelon III And IV Positions Antasari Banjarmasin State Islamic University - Amalia Husna; Zakhyadi Ariffin; Siti Faridah (International Journal of Management Research and Economics, 2024)
This research aims to determine and analyze the influence of psychological empowerment on employee performance, psychological empowerment on work engagement, work engagement on employee performance, the influence of psychological empowerment on employee performance through work engagement on educational staff affected by the equalization of Echelon III and IV positions at UIN Antasari Banjarmasin. This research is quantitative research with an explanatory research approach. This research method uses a questionnaire with 55 populations and all of them are sampled as respondents by testing hypotheses using SEM-PLS. The results of the study conclude that ( 1 ) psychological empowerment has a positive effect on employee performance, ( 2 ) psychological empowerment has a positive effect on work engagement, ( 3 ) work engagement has a positive effect on employee performance, and ( 4 ) psychological empowerment has a positive effect on employee performance through work engagement.